DESIGNING A MANAGEMENT SYSTEM FOR THE DEVELOPMENT OF HIGHER EDUCATION BASED ON AN INFORMATION-COGNITIVE APPROACH - Z. N. Ernazarov (American Journals, 2025)
This article examines the theoretical and methodological foundations for designing a management system for the development of higher education based on an information-cognitive approach. The study substantiates the systemic, cyclical, and integrative nature of management, emphasizing quality, information, and cognitive management as key components. The proposed model enables effective decision-making, reduces uncertainty, and ensures continuous improvement of higher education quality through the integration of information flows and cognitive analysis.
Keywords: Higher education development; information-cognitive approach; education management; quality management; cognitive management; information management; management system design.